Chemical Constituents from Vitex negundo (Linn.) of Nepalese Origin - Gautam, LM; Shrestha, SL; Wagle, P; Tamrakar, BM (Scientific World, 2010)
Vitex negundo Linn., belonging to family Verbenaceae, is an aromatic shrub distributed in lower part of Himalayan region of Nepal. In the ayurvedic system of medicine, it is used to control pain, inflammation and other related diseases. It contains many polyphenolic compounds, terpenoids, glycosidic iridoids and alkaloids. Bioactivity guided phytochemical investigation of methanolic extract of leaves of Vitex negundo resulted in the isolation of eight compounds under silicagel VLC, CC and preparative TLC. They were identified as negundoside, agnuside, vitegnoside, 7,8 dimethyl herbacetin 3-rhamnoside, 5,3'-dihydroxy-7,8,4'-trimethoxy flavanone, 5-hydroxy-3,6,7,3',4'-pentamethoxy flavone, 5,7 dihydroxy- 6,4' dimethoxy flavonone, and 5 hydroxy-7,4' dimethoxy flavone. The structures of pure compounds were elucidated by MP, Rf values, Co- TLC, Colour reactions (Cerric sulphate spray), mild acid hydrolysis and spectroscopic methods (Mass, UV, IR, 1H, 13C and 2 D NMR). All the isolated compounds were evaluated for their antimicrobial activities. They were found to have significant antibiotic activity against Bacillus subtilis, Staphylococcus aureus, Micrococcus pyogenes, Pseudomonas aeruginosa and E. coli. The compounds vitegnoside, and 7, 8 dimethyl herbacetin 3-rhamnoside have MIC 6.25mg/ml. Keywords: Vitex negundo; Verbenaceae; Chemical constituents; Bioassay; Analysis. DOI: 10.3126/sw.v6i6.2630 Scientific World, Vol. 6, No. 6, July 2008 27-32